Age-related Differences in Outcome and Severity of DIC in Children with Septic Shock and Purpura - Hazelzet, Jan A; Risseeuw-Appe, Inge M; Kornelisse, René F; Hop, Wim C J; Dekker, Ina; Joosten, Koen F M; Groot, Ronald de; Erik Hack, C (Thrombosis and Haemostasis, 1996)
We studied the influence of age on mortality and severity of clotting abnormalities in 79 children (median age: 3.1 years) with meningococcal sepsis. Parameters of coagulation and fibrinolysis and plasma levels of cytokines were prospectively measured on admission. The mortality rate was 27%. The age of survivors was significantly different from that of non-survivors (p = 0.013). With the exception of FVII, vWF and t-PA, parameters of coagulation and fibrinolysis, as well as plasma cytokine levels were related to outcome. Patients were divided in two groups: younger and older than median age. The mortality in children ≤3.1 years was 40% versus 13% in children >3.1 years (p = 0.006). In contrast to cytokine levels, which were not different between the two age groups, fibrinogen, prothrombin, factors V, VII, VIII, vWF, protein C, antithrombin, FDP, and the ratio PAI-l/t-PA were related to age, indicating a more severe coagulopathy in children ≤ 3.1 years despite a similar degree of inflammatory response. A relative deficiency of coagulation factors due to an immature state of the clotting system, as well as an inadequate fibrinolytic response, both related to age may have caused this more severe coagulative response in younger children, and may have contributed to the higher mortality rate.